Kelayakan media flash flipbook pada submateri darah - Ruqiah Ganda Putri Panjaitan; Astrid Maulidya; Yokhebed Yokhebed (IKIP PGRI Pontianak, 2022)
This study aims to determine the feasibility of flash flipbook as a medium for sub blood material learning. The research method is descriptive with survey and the research instrument is a validation sheet. The feasibility of flash flipbook was measured through material validity test and media validity test. The validation aspect of flash flipbook material consists of format, content, and language. The aspect of media validation from flash flipbook consists of general aspects, soft engineering, visual engineering, and audio communication. The results of flash flipbook validation obtained an average value of validation by material experts 3.35 valid criteria and the average value of validation by media experts 3.42 valid criteria. It can be concluded that flipbook flash is suitable to be used as a learning medium on sub blood material.